Serotyping and Genotyping of Salmonella Strains Isolated from Broilers, Chicken Carcasses Before and After Chilling, and Frozen Chicken Breasts Produced in the States of Mato Grosso do Sul and Santa Catarina, Brazil - SCA Machado (Revista Brasileira de Ciência Avícola, 2017)
The present study investigated the effectiveness of a single Salmonella prevention and control program applied in two different processing plants, located in the states of Mato Grosso do Sul (plant A) and Santa Catarina (Plant B), belonging to the same company, and identified Salmonella strain subtypes isolated from broilers, carcasses before and after chilling, and frozen chicken breasts. The Salmonella prevention and control program was 90% effective in plant A and 100% in plant B, considering a level of 10% positive samples per frozen chicken breast batch acceptable. A total of 128 strains were serotyped, being 10 from drag swabs, 31 from cloacal swabs, 83 from carcasses, and 4 from frozen chicken breasts. After serotyping analysis, 30 strains isolated at different processing steps and drag swabs, and three Salmonella Minnesota strains isolated in 2012 in plant A, were genotyped by PFGE. In plant A, the most frequently strain isolated was Salmonella Minnesota (90.35%), followed by Salmonella Newport (8.77%), and in Plant B, Salmonella Senftenberg (80%). Salmonella Minnesota strains were differentiated by PFGE into 19 pulsotypes distributed in three clusters. The phenotypic identification by serotyping of four strains diverged from their PFGE genotypic results. Most Salmonella Minnesota strains genotyped in plant A and the strains isolated from environmental samples in 2012 in the same broiler processing plant belong to a single cluster, confirming the dominance and persistence of this clone over time.